Subcutaneous Dirofilaria repens infection in an imported dog in Denmark - Kurt Buchmann; Per Walter Kania; Per Johansen (Acta Veterinaria Scandinavica)
Abstract Background The filarioid nematode Dirofilaria repens infects mainly dogs and is transmitted by vector mosquitoes when biting the definitive host. The parasite has mainly been reported from Eastern and Southern Europe, but during recent decades it has expanded its geographic range to some countries in Central and Northern Europe. Here, we report the finding of a fully mature female D. repens in a dog in Denmark. Case presentation A female specimen of the filarioid nematode Dirofilaria repens (superfamily Filarioidea, family Onchocercidae) was isolated from a ruptured subcutaneous nodule in an 18 months old Border Collie on the Danish island of Bornholm. The dog was born in Italy, where it lived for the first 3 months of its life, whereafter it was imported to Denmark via Switzerland. Species diagnosis was based on molecular methods (Polymerase chain reaction PCR and sequencing of ribosomal DNA (rDNA, ITS) and mitochondrial DNA (mtDNA, COX1, NADH) in combination with morphometric characterization. The viviparous nematode was relatively small (total length 102 mm, broadest width 0.6 mm). It had a prominent uterus containing numerous eggs at different embryonation stages, some of which showed fully developed microfilariae. Conclusions Dirofilaria repens was originally reported from Southern Europe and Asia, but during recent decades, it expanded its distribution area northwards, allowing autochthonous transmission to occur in Germany, Poland, Estonia, Latvia, Lithuania and Finland. The present report provides the first description from Denmark of a fully mature female worm in a dog imported from Italy. Known vectors include species of mosquitoes within the genera Aedes, Anopheles Coquillettidia and Culex, which are endemic in Denmark, reflecting the risk of future autochthonous transmission also in Denmark, where climatic conditions now allow larval development in the vectors. Although suspected to be an imported case, it cannot be excluded that the infection was contracted in Denmark.